2006
DOI: 10.1111/j.0014-3820.2006.tb01131.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Floral Traits Associated With Mating System Evolution in Leptosiphon (Polemoniaceae): An Analysis of Quantitative Trait Loci

Abstract: Mapping of quantitative trait loci (QTL) was used to investigate the genetic architecture of divergence in floral characters associated with the mating system, an important adaptive trait in angiosperms. Two species of Leptosiphon (Polemoniaceae), one strongly self-fertilizing (L. bicolor) and the other partially outcrossing (L. jepsonii), were crossed to produce F2 and both backcross progenies. For each crossing population, a linkage map was created using amplified fragment length polymorphism markers, and QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…QTL analyses of traits potentially involved in pre-or postzygotic isolating barriers in plants have repeatedly found that QTLs for different traits cluster in particular areas of the genome (Fishman et al, 2002;Hodges et al, 2002;Rieseberg et al, 2003;Bratteler et al, 2006;Goodwillie et al, 2006;Moyle, 2007), thus providing evidence for the occurrence of pleiotropy or linkage among QTLs for different traits. Whether such clustering of QTLs is due to pleiotropy or tight linkage is often unknown (Conner, 2002), but both cause strong correlations among the traits involved.…”
Section: Interactions Among Barriers: Ecological and Molecularmentioning
confidence: 99%
“…QTL analyses of traits potentially involved in pre-or postzygotic isolating barriers in plants have repeatedly found that QTLs for different traits cluster in particular areas of the genome (Fishman et al, 2002;Hodges et al, 2002;Rieseberg et al, 2003;Bratteler et al, 2006;Goodwillie et al, 2006;Moyle, 2007), thus providing evidence for the occurrence of pleiotropy or linkage among QTLs for different traits. Whether such clustering of QTLs is due to pleiotropy or tight linkage is often unknown (Conner, 2002), but both cause strong correlations among the traits involved.…”
Section: Interactions Among Barriers: Ecological and Molecularmentioning
confidence: 99%
“…QTL mapping studies have often found genomic regions that influence variation in multiple floral traits (for example, Juenger et al, 2000;Fishman et al, 2002;Goodwillie et al, 2006;Bouck et al, 2007). Pleitropy or tight linkage of QTLs that influence floral traits may constrain floral evolution in a hybrid zone.…”
Section: Genetic Architecture Of Floral Characteristicsmentioning
confidence: 99%
“…The genetic basis of the selfing syndrome has been studied using quantitative genetic approaches in three different genera, Mimulus, Leptosiphon, and Solanum (Lycopersicon) (Bernacchi and Tanksley, 1997;Lin and Ritland, 1997;Fishman et al, 2002;Georgiady et al, 2002;Goodwillie et al, 2006). In general, a moderate to large number of quantitative trait loci (QTL) affect individual floral traits, each with small to moderate effects.…”
Section: Introductionmentioning
confidence: 99%